Combined resistance training with aerobic training improves physical performance in patients with coronary artery disease: A secondary analysis of a randomized controlled clinical trial - Tim Kambic; Nejc Šarabon; Nejc Šarabon; Nejc Šarabon; Mitja Lainscak; Mitja Lainscak; Vedran Hadžić (Frontiers in Cardiovascular Medicine, 2022)
BackgroundThe efficacy of combined resistance training (RT) and aerobic training (AT) compared with AT alone is well established in cardiac rehabilitation (CR); however, it remains to be elucidated whether RT load (high load [HL] vs. low load [LL]) modifies the outcomes. The aim of our study was to investigate the effects of HL-RT and LL-RT combined with AT in comparison to AT alone on body composition and physical performance in patients with coronary artery disease (CAD) enrolled in phase II CR.MethodsWe randomized 79 patients with a stable CAD to 12 weeks of lower limb LL-RT + AT (35–40% of one repetition maximum [1-RM]; n = 28), HL-RT + AT (70–80% of 1-RM; n = 26), or AT (n = 25). Fifty-nine patients (75% men) with mean (standard deviation) age 61 (8) years and left ventricular ejection fraction 53 (9)% completed LL-RT (n = 19), HL-RT (n = 21) and AT (n = 19). Body composition and physical performance (upper and lower submaximal muscle strength, flexibility, balance, and mobility) were measured at baseline and post-training.ResultsTraining intervention had no significant impact on time × group interaction in the body composition measures. There was a significant time × group interaction for the gait speed test, chair sit-and-reach test, arm curl test, Stork balance test, up and go test, STS-5, and 6-min walk distance (p-values ≤ 0.001–0.04) following the training intervention. After the training intervention, HL-RT improved gait speed (+12%, p = 0.044), arm curl (+13%, p = 0.037), and time of Up and Go test (+9%, p < 0.001) to a greater extent compared with AT group, while there was a greater improvement in time of Up and Go test (+18%, p < 0.001) and time of five sit-to-stand tests (+14%, p = 0.016) following LL-RT when compared with AT. There were no differences between HL-RT and LL-RT in post-training improvement in any of the physical performance measures.ConclusionThe combination of AT with HL-RT or LL-RT promoted similar improvements in physical performance, which were superior to AT. Therefore, both types of combined AT and RT can be applied to patients with CAD.Clinical trial registration[https://clinicaltrials.gov/ct2/show/NCT04638764] Identifier [NCT04638764].